Perbandingan Alasan Penghapusan Pidana Untuk Subjek Hukum Korporasi di Belanda dan dalam Undang-Undang No 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Farhana Nabila Hanifah (Jurnal Syntax Admiration, 2024)
Regulations regarding the excuses of crime justification crimes will be regulated in the draf to criminal law code, regarding the justification excuses that are owned by individual swhorelated with the corporation which also can beused by the corporation in the same crime case. In the new KUHP bill, we are different from the old KUHP because the old KUHP still uses the Societas delinquere non potest principle, which means that corporations (legal entities) cannot commit criminal acts and cannot be held criminally accountable either. How ever, along with the development tof the era with the number of cases involving corporations as perpetrators of criminal acts, the Criminal Code that we currently use has been revised, with the National Criminal Code Bill. The change islocated in Article 45 paragraph 1 of the Draft Criminal Code, which states that corporations arecriminal subjects. This research is normative juridical research that uses a Comparative Approachand a Statute Approach. The legal materials used are primary legal materials and secondary legalmaterials. The results of this study are that the Draft Criminal Code and the Special Law have notregulated the criminal liability of corporations committed by the private sector. Where in the Netherlands these arrangements have been regulated in the Dutch Penal Code in Article 328ter paragraph (1) and Article 328ter paragraph (2).